Structuring Sovereignty: Islam and Modernity in the Mosque of Muhammad ‘Ali Pasha - GhaneaBassiri, Kambiz (Material religion, 2020)
The monumental Alabaster Mosque of the Ottoman-appointed governor of Egypt Muhammad ‘Ali Pasha (r. 1805-1848) has been varyingly examined as a visual representation of the Pasha’s political ambitions, modernizing spirit, nationalist aspirations, and cosmopolitanism. Scholars have generally sought to explain the significance of Muhammad ‘Ali’s mosque through such structuring concepts as modernity and nationalism, but questions remain as to why Muhammad ‘Ali sought to embody his political agenda and personal ambitions by monumentalizing a place of worship. What about the mosque as an Islamic object and a place of worship was significant for conceptualizing modernity and nationalism in early-nineteenth-century Egypt? By approaching the mosque as a structuring institution of Islam, this article highlights the distinctiveness of the mosque as a site and an object through which Muhammad ‘Ali negotiated varying conceptions of sovereignty, power, and national identity at a time of transition in Egyptian history.